Performance Analysis Of An Iot-Based 3-Dof Robotic Arm: A Case Study On Latency And Payload Variations - K Umurani; AR Nasution; MH Gultom; TA Putra; R Efrida; RD Fauzan (Journal of Telecommunication and Electrical Scientific, 2025)
Digital transformation in the manufacturing sector demands the integration of efficient and responsive robotic systems. This study aims to analyze the performance of an Internet of Things (IoT)-based 3-Degree of Freedom (DOF) robotic arm, focusing on latency testing and payload variations. Conducted at the UMSU Mechanical Engineering Laboratory, the research utilizes an ESP32 microcontroller as the central processing unit and the Blynk platform as the wireless control interface. The robot's physical structure was fabricated using 3D printing technology, while joint actuation is powered by MG996R servo motors with an 11 kg/cm torque capacity. Electrical parameters were measured using a Fluke 17B+ digital multimeter to precisely monitor current consumption. Performance evaluation encompasses a multi-parameter analysis integrating information technology aspects, such as IoT network latency, with mechanical aspects including payload variations (15g, 35g, and 50g) and pick-and-place operational success. The IoT-based 3-DOF robotic arm control system was successfully implemented. The robot responded to commands within 0.5–0.9 seconds on a stable network. Performance is highly dependent on Wi-Fi signal quality, with latency increasing to >1 second at extended distances or when obstructed.